Natural history of non-polyglutamine CACNA1A disease in Austria - Indelicato, Elisabetta; Nachbauer, Wolfgang; Amprosi, Matthias S.; Maier, Sarah; Unterberger, Iris; Delazer, Margarete; Kaltseis, Katharina; Kiechl, Stefan; Broessner, Gregor; Baumann, Matthias; Boesch, Sylvia (Journal of neurology, 2024)
Background and objectives Non-polyglutamine CACNA1A variants underlie an extremely variable phenotypic spectrum encompassing developmental delay, hemiplegic migraine, epilepsy, psychiatric symptoms, episodic and chronic cerebellar signs. We provide our experience with the long-term follow-up of CACNA1A patients and their response to interval therapy. Methods Patients with genetically confirmed non-polyglutamine CACNA1A disease were prospectively followed at the Center for Rare Movement Disorders of the Medical University of Innsbruck from 2004 to 2024. Results We recruited 41 subjects with non-polyglutamine CACNA1A disease, of which 38 (93%) familial cases. The mean age at the first examination was 35 ± 22 years. Disease onset was in the childhood/adolescence in 31/41 patients (76%). Developmental delay and episodic symptoms were the first disease manifestation in 9/41 (22%) and 32/41 (78%) patients respectively. Chronic neurological signs encompassed a cerebellar syndrome in 35/41 (85%), which showed almost no progression during the observation period, as well as cognitive deficits in 9/20 (45%, MOCA test score < 26), psychiatric and behavioral symptoms in 11/41(27%). Seizures occurred in two patients concomitant to severe hemiplegic migraine. At the last visit, 27/41 patients (66%) required an interval prophylaxis (including acetazolamide, flunarizine, 4-aminopyridine, topiramate), which was efficacious in reducing the frequency and severity of episodic symptoms in all cases. In one patient in his 70ies with progressively therapy resistant hemiplegic migraine, treatment with the anti-CGRP antibody galcanezumab successfully reduced the frequency of migraine days from 4 to 1/month. Conclusions Non-polyglutamine CACNA1A disease show an evolving age-dependent presentation. Interval prophylaxis is effective in reducing the burden of episodic symptoms.